TEACHER EVALUATION STRATEGIES FOR STUDENTS’ NEWS TEXT WRITING SKILLS - Sumayyah Azzahra; Asih Riyanti; Gita Minarti; Nurjihan Fadhilah; PutriAmalia; Noranisa (STKIP Citra Bakti, 2026)
Appropriate evaluation strategies are essential in teaching news text writing because not all students have the same ability to organize ideas, structure, and linguistic rules. This study aims to describe the evaluation strategies implemented by teachers on the news text writing skills of seventh-grade students at SMPIT Ulul Albab Tarakan. This research employed a descriptive qualitative approach with seventh-grade students and Indonesian language teachers as the subjects. Data were collected through observation, interviews, and questionnaires. The results showed that the teacher implemented process-based evaluation strategies using contextual approaches, authentic assessment, rubrics, peer assessment, and portfolios. The majority of students (82.8%–100%) reported understanding the teacher's explanations, had received assignments to write news texts, and received feedback for improvement. However, 65.5% of students stated that the assessment methods lacked variety, and another 65.5% reported that the writing results were never discussed together in class. The main difficulties faced by students were finding ideas, developing topics, structuring the news text, and using appropriate language. In conclusion, the evaluation strategies applied by the teacher have helped improve students' understanding and writing skills, but there is a need for greater variety in assessment techniques, more classroom discussion of writing results, and more equitable distribution of motivation.